Preparation method of nanowire for strengthening gas turnover and application of nanowire to electrocatalytic synthesis of ammonia
By synthesising ammonia through electrocatalytic nitrate reduction, the phosphorus embedded strategy forms cationic sites, modulates local cation enrichment to improve the interfacial tension of microbubble, solving the problem of hydrogen microbubble hindering active sites, and achieving high current density and long-term stable ammonia synthesis.
Patent Information
- Application Number
- CN202411484667.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-23
AI Technical Summary
During the electrocatalytic nitrate reduction and synthesis of ammonia, the hydrogen microbubbles produced by local hydrogen evolution reaction hinder the contact of active sites with the electrolyte, resulting in slow reaction kinetics, low current density, and high overpotential problems.
The phosphorus embedded strategy forms cationic sites on the surface of transition metal nanowires, modulate local cation enrichment to improve the interface tension of microbubble, strengthen local bubble turnover, and form highly active catalytic sites on the surface of nanowires.
A high current density, high selectivity, and long-term stable ammonia synthesis is achieved, which improves the performance of electrocatalytic nitrate reduction reaction.
Smart Images

Figure CN119530853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing nanowires for strengthening gas turnover and application in electrocatalytic synthesis of ammonia, belonging to the fields of material science and electrocatalysis. Background Art
[0002] Ammonia is an indispensable chemical in agriculture and industry. Currently, the global synthetic ammonia industry mainly relies on the Haber-Bosch process. This process has been the standard method for ammonia production since the early 20th century. It can synthesize ammonia from nitrogen and hydrogen under high temperature (about 500°C) and high pressure (about 20-30 MPa). However, the source of high-purity hydrogen in this process usually relies on the steam reforming (SMR) process of natural gas, which produces a large amount of carbon dioxide emissions. The mining and transportation of natural gas resources also bring environmental and economic uncertainties. The high temperature and high pressure conditions of the Haber-Bosch process also consume a large amount of fossil fuels, causing the synthetic ammonia industry to consume about 2% of the earth's energy each year and emit more than 300 million tons of carbon dioxide, which puts great pressure on the environment and further exacerbates global climate change. In addition, due to the economies of scale of the Haber-Bosch process, most ammonia production facilities are large and centralized, which limits the flexibility and decentralization of ammonia production and is not suitable for areas with remote geographical locations or lack of industrial infrastructure.
[0003] With the continuous development of renewable energy technology, electrocatalytic nitrogen reduction reaction (NRR) ammonia synthesis can be carried out at room temperature and pressure, with the advantages of fast start-up, flexible operation, clean and pollution-free, and is regarded as a potential clean ammonia synthesis route. However, nitrogen molecules have the characteristics of high bond energy and low solubility, which makes the competitive hydrogen evolution reaction in the electrocatalytic nitrogen reduction reaction system strong, and the ammonia synthesis yield and Faraday efficiency still need to be improved. The electrocatalytic nitrate reduction reaction (NO3RR) uses nitrate as a nitrogen source. Compared with nitrogen, nitrate has a more active N=O bond (204kJ / mol), which makes it easier to achieve high Faraday efficiency and high ammonia yield in the electrocatalytic system. In addition, considering that nitrate in the environment may cause an imbalance in the nitrogen cycle in water bodies and affect the structure and function of aquatic ecosystems, the synthesis of ammonia through nitrate reduction can not only achieve green and clean chemical production, but also contribute to resource reuse and pollution control.
[0004] As the main competitive reaction of electrocatalytic nitrate, the hydrogen evolution reaction produces microbubbles, which will produce a gas layer at the electrocatalyst-electrolyte interface, hindering the reaction active sites and thus reducing the activity of the ammonia synthesis reaction. Although some studies have reported catalysts with a Faraday efficiency close to 100% under ideal conditions, considering that factors such as power fluctuations, temperature changes, and reactant consumption in real industrial environments may cause the reaction to deviate from the optimal conditions, it is difficult to completely avoid the competitive hydrogen evolution reaction in the synthesis of ammonia in an industrial environment. Therefore, industrial-grade ammonia synthesis catalysts with fast interfacial gas turnover rate, good stability, and high electrocatalytic performance are urgently needed to be developed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing nanowires with enhanced gas turnover and its application in the field of electrocatalytic nitrate reduction to synthesize ammonia, so as to solve the problem that hydrogen microbubbles generated by local hydrogen evolution reaction in the process of nitrate reduction to synthesize ammonia hinder the contact between active sites and electrolytes, thereby causing slow reaction kinetics, low current density, high overpotential and other problems. Through the phosphorus embedding strategy, cation-philic sites are formed on the surface of transition metal nanowires, local cation enrichment is modulated to improve microbubble interfacial tension, strengthen local bubble turnover, form highly active catalytic sites on the surface of nanowires, improve the performance of electrocatalytic nitrate reduction reaction, and achieve high current density, high selectivity, and long-term stable ammonia synthesis.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing nanowires with enhanced gas circulation, the method comprising the following steps:
[0007] 1) Clean and dry the transition metal substrate thoroughly;
[0008] 2) using a strong oxidant to perform oxidation etching on the surface of a transition metal substrate to obtain a metal oxide nanowire precursor;
[0009] 3) performing phosphating treatment on the metal oxide nanowire precursor obtained in step 2) to obtain a phosphorus-embedded metal oxide nanowire precursor;
[0010] 4) Electro-reducing the phosphorus-embedded metal oxide nanowire precursor obtained in step 2) to obtain nanowires with enhanced gas circulation.
[0011] Furthermore, the transition metal substrate is one of foamed copper, foamed nickel or foamed iron.
[0012] Furthermore, the cleaning method is: soaking in 0.05M HCl for 10 minutes, and repeatedly rinsing with 30°C deionized water and anhydrous ethanol; the drying method is vacuum drying in an oven at 60°C for 10 hours.
[0013] Furthermore, the strong oxidant is 1M NaOH+0.1M (NH4)2S2O8, and the dosage is per 1cm 2 Transition metal substrates require 10 mL of a strong oxidant.
[0014] Furthermore, the phosphating treatment is to place sodium hypophosphite upstream of the tube furnace in an amount of 1 cm 2 The transition metal substrate required 0.3 g, and the metal oxide nanowire precursor was placed downstream and heated at 1 °C min in an argon atmosphere. -1 After heating to 240°C at a heating rate of , the holding time is 1-3 hours.
[0015] Furthermore, the electroreduction process is to use a constant current method to reduce for 2 hours in a 1M KOH electrolyte environment of a single-cell three-electrode system, and the current applied to the electrode per square centimeter is 150 mA.
[0016] In a second aspect, the present invention provides a nanowire for enhancing gas circulation.
[0017] In a third aspect, the present invention provides a catalyst for the electrocatalytic reduction of nitrate to synthesize ammonia using nanowires that enhance gas turnover.
[0018] The present invention fully cleans and dries a transition metal substrate, performs oxidation etching on the surface of the transition metal substrate using a strong oxidant to obtain a metal oxide nanowire precursor; performs phosphating treatment on the obtained metal oxide nanowire precursor to obtain a phosphorus-embedded metal oxide nanowire precursor; and electro-reduces the obtained phosphorus-embedded metal oxide nanowire precursor to obtain nanowires with enhanced gas turnover, which can be used in the field of electrocatalytic nitrate reduction to achieve efficient and stable ammonia synthesis.
[0019] The advantages of the present invention are:
[0020] (1) The method is simple. The method for preparing nanowires for enhancing gas turnover provided by the present invention has the advantages of simple operation steps, short preparation process, simple synthesis process, easy operation, strong electrocatalytic activity, high selectivity, etc. It does not require large-scale equipment, and the raw materials are easily available, which is conducive to large-scale production;
[0021] (2) Good catalytic performance. The nanowires for enhancing gas turnover provided by the present invention maintain a Faradaic efficiency of more than 95% during the electrocatalytic reduction of nitrate to synthesize ammonia, and achieve 600 mA cm at a potential of -0.5 V vs. RHE. -2 The above ammonia synthesis current density is of great significance to the industrial promotion of high-efficiency and high-activity electrocatalytic ammonia synthesis.
[0022] (3) Strong scalability. The method for preparing nanowires for enhancing gas turnover provided by the present invention can be extended to the development of other two-phase reaction catalysts. By implementing an appropriate phosphorus doping strategy on the surface of the nanowires, the modulation of hydrogen micro-nano bubbles is achieved, the coverage barrier of hydrogen bubbles on the active centers is weakened, and the activity of solid-liquid two-phase reactions is improved. By improving the substrate conditions, a nanowire structure for enhancing gas turnover can be formed on different transition metals, and the catalytic effect is significantly improved, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a transmission electron microscope image of the nanowires that enhance gas turnover;
[0024] Figure 2 This is a comparison of the X-ray diffraction of nanowires that enhance gas circulation and ordinary nanowires;
[0025] Figure 3 This is a comparison of the X-ray photoelectron spectra of nanowires that enhance gas circulation and ordinary nanowires;
[0026] Figure 4 This is a Faraday efficiency diagram of nanowires with enhanced gas circulation and ordinary nanowires at different potentials;
[0027] Figure 5 is the current density diagram of the nanowire with enhanced gas circulation and the ordinary nanowire at different potentials;
[0028] Figure 6 The current density and Faraday efficiency of nanowires with different phosphorus doping levels for enhanced gas circulation at -0.2V vs. RHE potential;
[0029] Figure 7 It is a graph of the ammonia synthesis rate of metal-based nanowires with enhanced gas turnover at a potential of -0.2 V vs. RHE. DETAILED DESCRIPTION
[0030] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0031] Embodiment 1:
[0032] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere. -1The temperature was heated to 240 °C at a rate of 1.5 h and maintained at that temperature for 1.5 h. After cooling naturally, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The nanowires with enhanced gas circulation were prepared by reduction under a constant current of 2 hours. The microstructure of the nanowires with enhanced gas circulation was characterized by transmission electron microscopy. Figure 1 As shown, the nanowires that enhance gas turnover present a typical nanowire structure with a diameter of about 20-30 nm.
[0033] Embodiment 2:
[0034] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere. -1 The temperature was heated to 240 °C at a rate of 1.5 h and maintained at that temperature for 1.5 h. After cooling naturally, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The nanowires with enhanced gas circulation were reduced under a constant current of 2 hours. The phase composition of the obtained nanowires with enhanced gas circulation was characterized by X-ray diffraction, such as Figure 2 As shown, the nanowires with enhanced gas turnover are mainly composed of Cu, and there are no obvious X-ray diffraction peaks of CuP compounds or P particles, which proves that P is dispersed and embedded in Cu.
[0035] Embodiment 3:
[0036] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere. -1 The temperature was heated to 240 °C at a rate of 1.5 h and maintained at that temperature for 1.5 h. After cooling naturally, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The surface species valence states of the obtained nanowires with enhanced gas turnover were characterized by X-ray photoelectron spectroscopy, such as Figure 3 As shown, the surface Cu is 0 valence and is in a metallic state.
[0037] Embodiment 4:
[0038] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere. -1 The temperature was heated to 240 °C at a rate of 1.5 h and maintained at that temperature for 1.5 h. After cooling naturally, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The nanowires with enhanced gas turnover were obtained by reduction under a constant current of 2 h.
[0039] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and dried again, and then charged with 150mA cm in a 1M KOH electrolyte environment of a single cell three-electrode system. -2 The nanowires were reduced under a constant current of 2 h to obtain ordinary nanowires.
[0040] The performance of the two materials in nitrate reduction and ammonia synthesis was evaluated in an H-type electrolytic cell. Different cathode potentials were applied to the system and the Faraday efficiency and partial current density at the corresponding potential were measured after 30 minutes. Figure 4 As shown in Figure 2, the nanowires with enhanced gas circulation exhibited higher Faraday efficiency than ordinary nanowires at various potentials from -0.5 to 0 V vs. RHE, and reached the maximum Faraday efficiency (96.76%) at -0.2 V vs. RHE. Figure 5 As shown in the figure, the nanowires with enhanced gas turnover showed a larger synthetic ammonia current density than ordinary nanowires at various potentials from -0.5 to 0 V vs. RHE, reaching -644.35 mA cm at a potential of -0.5 V vs. RHE. -2 .
[0041] Embodiment 5:
[0042] Take 1×1cm 2The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere. -1 The temperature was heated to 240 °C at a rate of 100 °C and maintained at this temperature for 1 h. After natural cooling, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The same method was adopted, and the temperature holding time was changed to 1.5, 2, 2.5, and 3 hours respectively, to obtain nanowires with enhanced gas turnover of different phosphorus doping degrees: P 1.5 , P2, P 2.5 , P3.
[0043] The performance of several materials in nitrate reduction for ammonia synthesis was evaluated in an H-type electrolytic cell. A cathode potential of -0.2 V vs. RHE was applied to the system and the Faraday efficiency and ammonia yield at the corresponding potential were measured after maintaining the potential for 30 minutes. Figure 6 As shown, the temperature is maintained for 1.5 hours during the phosphating process. 1.5 The sample showed the highest ammonia synthesis rate, reaching 13.95 mg h -1 cm -2 , the Faraday efficiency is 96.76%; the temperature is maintained for 2.5 hours during the phosphating process. 2.5 The sample showed the highest Faradaic efficiency of 97.31% and an ammonia synthesis rate of 10.32 mg h -1 cm -2 In contrast, P 1.5 The ammonia synthesis rate of the sample is much higher than that of P 2.5 samples, and the Faraday efficiency is close, so P 1.5 Samples are preferred.
[0044] Embodiment 6:
[0045] Take 1×1cm 2 The foamed copper was soaked in 0.05M HCl for 10 min, then repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and the surface impurities were removed and then dried in an oven at 60℃ under vacuum for 10 hours; the foamed copper was immersed in 1M NaOH+0.1M (NH4)2S2O8 solution for 30 min; after being taken out, it was repeatedly rinsed with 30℃ deionized water and anhydrous ethanol, and then dried again and placed in the downstream of the tube furnace, and 0.3g sodium hypophosphite was placed upstream of the tube furnace, and heated at 1℃ min under argon atmosphere.-1 The temperature was heated to 240 °C at a rate of 1.5 h and maintained at that temperature for 1.5 h. After cooling naturally, the electrolyte was charged with 150 mA cm-1 in a 1 M KOH electrolyte environment in a single cell three-electrode system. -2 The nanowires (Cu) with enhanced gas circulation were obtained by reducing them under a constant current of 2 hours. The same method was adopted to change the initial materials to foam nickel, foam iron, and foam titanium, respectively, to obtain nanowires with enhanced gas circulation based on different metals: Ni, Fe, and Ti.
[0046] The performance of several materials in nitrate reduction for ammonia synthesis was evaluated in an H-type electrolytic cell. A cathode potential of -0.2 V vs. RHE was applied to the system and the Faraday efficiency and ammonia yield at the corresponding potential were measured after maintaining the potential for 30 minutes. Figure 7 As shown, the gas turnover-enhanced nanowire Cu made with copper foam as the transition metal substrate exhibits a better ammonia synthesis rate than both Ni and Fe, so Cu is the preferred option.
[0047] Experimental results
[0048] Through the working condition exploration and performance comparison of the above embodiments, the nanowires with enhanced gas turnover effectively enhance the activity of the electrocatalytic ammonia synthesis reaction due to the surface phosphorus embedding strategy, and can efficiently synthesize ammonia with a Faraday efficiency of more than 95% under fluctuating working conditions. It has excellent catalytic performance and has good prospects for industrial promotion.
[0049] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing nanowires with enhanced gas circulation, characterized in that: The method comprises the following steps: 1) Clean and dry the transition metal substrate thoroughly; 2) using a strong oxidant to perform oxidation etching on the surface of a transition metal substrate to obtain a metal oxide nanowire precursor; 3) performing phosphating treatment on the metal oxide nanowire precursor obtained in step 2) to obtain a phosphorus-embedded metal oxide nanowire precursor; 4) Electro-reducing the phosphorus-embedded metal oxide nanowire precursor obtained in step 2) to obtain nanowires with enhanced gas circulation.
2. A nanowire for enhancing gas circulation according to claim 1, characterized in that: The transition metal substrate is one of foamed copper, foamed nickel or foamed iron.
3. A nanowire for enhancing gas circulation according to claim 1, characterized in that: The cleaning method is: soaking in 0.05M HCl for 10 minutes, and repeatedly washing with 30°C deionized water and anhydrous ethanol; the drying method is vacuum drying in an oven at 60°C for 10 hours.
4. A nanowire for enhancing gas circulation according to claim 1, characterized in that: The strong oxidant is 1M NaOH + 0.1M (NH4) 2S2O8, and the dosage is 1cm 2 Transition metal substrates require 10 mL of a strong oxidant.
5. A nanowire for enhancing gas circulation according to claim 1, characterized in that: The phosphating treatment is to place sodium hypophosphite upstream of the tube furnace in an amount of 1 cm 2 The transition metal substrate required 0.3 g, and the metal oxide nanowire precursor was placed downstream and heated at 1 °C min in an argon atmosphere. -1 After heating to 240°C at a heating rate of , the holding time is 1-3 hours.
6. A nanowire for enhancing gas circulation according to claim 1, characterized in that: The electroreduction process is to use a constant current method to reduce for 2 hours in a 1M KOH electrolyte environment of a single-cell three-electrode system, and the current applied to the electrode per square centimeter is 150 mA.
7. A nanowire for enhancing gas circulation prepared according to any one of claims 1 to 6.
8. Use of a nanowire for enhancing gas turnover prepared by the method according to any one of claims 1 to 6 as a catalyst for electrocatalytic nitrate reduction to synthesize ammonia.
Citation Information
Patent Citations
Preparation method of three-dimensional self-supported Cu3PNW@CoFeP composite material
CN109876846A
Nanowire-shaped copper diphosphide as well as preparation method and application thereof
CN112537760A
Three-dimensional layered nano-array structure copper-based material and preparation method and application thereof
CN113789543A
Self-supporting Cu3P-based heterojunction electrocatalyst as well as preparation method and application thereof
CN114318408A
Preparation method and application of gradient copper phosphide / copper oxide / foamy copper lithium metal anode current collector
CN116960357A